ANALISIS STRATEGI PEMASARAN PRODUK PEMBIAYAAN PEMBELIAN BARANG PADA BANK SUMSEL BABEL SYARIAH - Hasan, Ikit; Juliani, Deka (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2023)
Abstract Marketing strategies include marketing strategy, marketing tactics and value. This study uses a qualitative descriptive approach by collecting actual information from existing symptoms. Data collection techniques used are interviews, observation and documentation. The marketing strategy implemented by the Sumsel Babel Bank Syariah Muara Kelingi Sub-branch is to use the Marketing Building concept, namely product strategy, price strategy, place strategy and promotion strategy. The marketing strategy for the product is directed to the Goods Purchase Financing (PPB) product using a Murabahah contract which is a superior product at the Muara Kelingi Syariah Sub-branch of Bank Sumsel Babel. Pricing is carried out by the Bank in accordance with a mutual agreement between the Bank and the customer or prospective customer which is explained in detail at the beginning when the contract will occur. Keywords: Marketing Strategy, Goods Purchase Financing Products